2018
DOI: 10.1187/cbe.17-11-0229
|View full text |Cite
|
Sign up to set email alerts
|

Becoming a “Science Person”: Faculty Recognition and the Development of Cultural Capital in the Context of Undergraduate Biology Research

Abstract: We argue that cultural capital plays an underexamined role in students’ recognition as budding scientists by faculty. By triangulating interview data from undergraduates and faculty mentors in a multi-institutional biology research network, we identified a set of intersecting domains of capital that help render students recognizable to faculty. We argue that faculty recognition often reflects a (mis)alignment between the cultural capital that students possess and display and what faculty expect to see. To unde… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
46
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 43 publications
(51 citation statements)
references
References 61 publications
4
46
0
1
Order By: Relevance
“…Indeed, we agree that the responsibility should be placed on the system to change and not on the student. In order to create sustainable change with regard to who gets to participate in research, we posit that science faculty need to value scientific research cultural capital that does not align with what is traditionally valued by academia (Thompson & Jensen-Ryan, 2018). We argue that it may be unethical for faculty to rely on the unwritten rules as a way to select students into their lab if such rules are only available to a select, potentially more privileged, group of students.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Indeed, we agree that the responsibility should be placed on the system to change and not on the student. In order to create sustainable change with regard to who gets to participate in research, we posit that science faculty need to value scientific research cultural capital that does not align with what is traditionally valued by academia (Thompson & Jensen-Ryan, 2018). We argue that it may be unethical for faculty to rely on the unwritten rules as a way to select students into their lab if such rules are only available to a select, potentially more privileged, group of students.…”
Section: Discussionmentioning
confidence: 99%
“…While this is likely already happening, especially given the number of students in our study who said that they found out about research experiences through faculty and graduate students, it is possible that faculty and graduate students are only sharing this information with undergraduates who already have high levels of cultural capital (for example, those who come asking about how to find undergraduate research or those who know to ask faculty specifically about the research that they do). Thompson and Jensen-Ryan (2018) suggested that faculty recognition and cultural capital operate in a positive feedback loop, which can create consequences for students who do not enter undergraduate science disciplines with forms of cultural capital recognized by scientists. That is, faculty are more likely to recognize students who possess cultural capital and facilitate students' access to additional opportunities, such as undergraduate research experiences, which will in turn build additional scientific cultural capital (Thompson & Jensen-Ryan, 2018).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Including undergraduates can both facilitate student learning about research design and analysis and free faculty to dedicate time to other research activities-a two-for-one advantage of merging experiential learning with innovative and productive research (Bowne et al, 2011). As BRNs increasingly include undergraduates, students have the opportunity to contribute to scientific knowledge production, interact and share insights with students and faculty at other institutions, and develop scientific identity and cultural capital (Bowne et al, 2011;Thompson et al, 2016;Thompson and Jensen-Ryan, 2018). Undergraduate BRNs also effectively prepare student for scientific careers (Simmons et al, 2016).…”
Section: Undergraduate Involvement In Networked Biology Researchmentioning
confidence: 99%
“…The modern educational paradigm and changes in the functionality of the educational process offer new opportunities through mentored experience. Mentorship has generated considerable recent research interest [15][16][17]. Mentoring models are extremely diverse [18][19][20][21], but their application is not always systematized.…”
Section: Introductionmentioning
confidence: 99%